Antifungal Activities and Cytotoxicity Studies of Six New Azasordarins - Herreros, Esperanza (American Society for Microbiology, 2001)
GW 471552, GW 471558, GW 479821, GW 515716, GW 570009, and GW 587270 are members of a new family of sordarin derivatives called azasordarins. The in vitro activities of these compounds were evaluated against clinical isolates of yeasts, including Candida albicans, Candida non-albicans, and Cryptococcus neoformans strains. Activities against Pneumocystis carinii, Aspergillus spp., less common molds, and dermatophytes were also investigated. Azasordarin derivatives displayed significant activities against the most clinically important Candida species, with the exception of C. krusei. Against C. albicans, including fluconazole-resistant strains, MICs at which 90% of the isolates tested are inhibited (MIC(90)s) were 0.002 μg/ml with GW 479821, 0.015 μg/ml with GW 515716 and GW 587270, and 0.06 μg/ml with GW 471552, GW 471558, and GW 570009. The MIC(90)s of GW 471552, GW 471558, GW 479821, GW 515716, GW 570009, and GW 587270 were 0.12, 0.12, 0.03, 0.06, 0.12, and 0.06 μg/ml, respectively, against C. tropicalis and 4, 0.25, 0.06, 0.25, 0.5, and 0.5 μg/ml, respectively, against C. glabrata. In addition, some azasordarin derivatives (GW 479821, GW 515716, GW 570009, and GW 58720) were active against C. parapsilosis, with MIC(90)s of 2, 4, 4, and 1 μg/ml, respectively. The compounds were extremely potent against P. carinii, showing 50% inhibitory concentrations of ≤0.001 μg/ml. However Cryptococcus neoformans was resistant to all compounds tested (MIC > 16 μg/ml). These azasordarin derivatives also showed significant activity against emerging fungal pathogens, which affect immunocompromised patients, such as Rhizopus arrhizus, Blastoschizomyces capitatus, and Geotrichum clavatum. Against these organisms, the MICs of GW 587270 ranged from 0.12 to 1 μg/ml, those of GW 479821 and GW 515716 ranged from 0.12 to 2 μg/ml, and those of GW 570009 ranged from 0.12 to 4 μg/ml. Against Fusarium oxysporum, Scedosporium apiospermum, Absidia corymbifera, Cunninghamella bertholletiae, and dermatophytes, GW 587270 was the most active compound, with MICs ranging from 4 to 16 μg/ml. Against Aspergillus spp., the MICs of the compounds tested were higher than 16 μg/ml. The in vitro selectivity of azasordarins was investigated by cytotoxicity studies performed with five cell lines and primary hepatocytes. Concentrations of compound required to achieve 50% inhibition of the parameter considered (Tox(50)s) of GW 570009, GW 587270, GW 479281, and GW 515716 in the cell lines ranged from 60 to 96, 49 to 62, 24 to 36, and 16 to 38 μg/ml, respectively. The cytotoxicity values of GW 471552 and GW 471558 were >100 μg/ml for all cell lines tested. Tox(50)s on hepatocytes were in the following order: GW 471558 > GW 471552 > GW 570009 > GW 587270 > GW 515716 > GW 479821, with values ranging from higher than 100 μg/ml to 23 μg/ml. The cytotoxicity results obtained with fully metabolizing rat hepatocytes were in total agreement with those obtained with cell lines. In summary, the in vitro activities against important pathogenic fungi and the selectivity demonstrated in mammalian cell lines justify additional studies to determine the clinical usefulness of azasordarins.